Die Wurzeln der Entspannung : Der konzeptionelle Ursprung der Ost- und Deutschlandpolitik Willy Brandts in den fünfziger Jahren - Schmidt, Wolfgang (Vierteljahrshefte für Zeitgeschichte, 2003)
For many years, Willy Brandt's policy on Germany and her relations to Eastern Europe has been regarded as a mere reaction to the building of the Berlin Wall in 1961. In the view of the author, however, the roots of detente can be traced back to the 1950s. Many of Brandt's speeches and articles reveal that he had started to map out the basic ideas of his later Ostpolitik as early as 1955. Even then was convinced that the two superpowers shared a common interest in avoiding mutual destruction in a nuclear war. Therefore, they were, in Brandt's view, forced to seek a policy of coexistence and detente. As he assumed there to be a nuclear stalemate between the United States and the Soviet Union, Brandt saw, long before 1961, that German unity could only be restored within the framework of a peaceful solution of the East-West-conflict. In order to promote the transformation of the communist system in the long run, Brandt favoured a policy which gave priority to economic, scientific and cultural exchange, and to humanitarian relief across the iron curtain, rather than pursuing an illusionary policy of reunification, as had been followed both by the CDU/CSU under Adenauer and by the SPD under Ollenhauer. Brandt aimed at preserving the coherence of the divided nation in both parts of Germany. Hence, Willy Brandt pleaded for extending contact and technical agreements between the governments in Bonn and East Berlin from the 1950s. (Vierteljahrshefte für Zeitgeschichte / FUB)